Strategi Pemasaran pada UMKM Berbasis Kuliner (Studi Kasus: UMKM Siti Hajar Kota Pekanbaru) - Meilany, Merry; Winario, Mohd (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Marketing strategy is the implementation of business steps which are a manifestation of achieving business success. This strategy is very important considering that no matter how good the segmentation, target market and market position are, it will not work if the right strategy is not followed. This research uses a qualitative descriptive research approach. Data collection techniques using observation, interviews and documentation techniques. Based on the results and discussion of research that has been put forward regarding the marketing strategy of MSME Siti Hajar Pekanbaru, it can be concluded that MSME Siti Hajar Pekanbaru uses the 4P Marketing Mix which consists of product strategy with products that are packaged well, price ) with affordable prices, strategic locations, and regular promotions and utilizing technology. UMKM Siti Hajar also analyzes strengths and weaknesses (internal factors) as well as opportunities and threats (external factors) using SWOT. MSME Siti Hajar Pekanbaru maintains cash flow, widens the target market, continues to innovate by developing a variety of food flavors, maximizing social media, and creating a marketplace. MSME Siti Hajar Pekanbaru has culinary products that are quality, healthy, and priced according to product quality, distribution places are affordable to the public, and have carried out promotions through social media.